Corporate Venture Capital and Sport-Tech Enterprises: Innovation and Internationalization in an Emerging Economy Context - Chankuna, Dittachai (Organizations and Markets in Emerging Economies, 2026)
This study examines how different orientations of corporate venture capital (CVC) investment are associated with the strategic development of sport-tech firms in an emerging economy context. Using a longitudinal dataset of 48 Thai sport-tech firms and 73 CVC transactions between 2005 and 2025, the analysis focuses on two strategic outcomes: technology portfolio diversification and international market expansion. The results indicate that technology-oriented CVC is positively associated with broader technology portfolios, while foreign-oriented CVC is positively associated with wider geographic market presence. At the same time, the findings show that the strength of these relationships varies depending on the level of industry and cultural distance between investors and portfolio firms, suggesting that contextual compatibility influences the effectiveness of investment partnerships. The study adopts a mechanism-focused perspective that examines how strategic investment relationships may facilitate knowledge transfer and market access within CVC-backed firms. By applying the interorganizational learning framework to the sport-tech sector, the research extends existing corporate venture capital literature to an underexplored industry within an emerging economy context. The findings also provide practical insights for entrepreneurs, corporate investors, and policymakers seeking to leverage corporate venture capital as both a financial and strategic resource for innovation and international market participation.
Keywords: International investment; International business administration; Corporate culture; Sport-tech firm